IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (Studi Empiris pada Kecamatan Kuantan Tengah Kab. Kuantan Singingi) - Ilham, Elfi; Kamaliah, Kamaliah; Rifqi, Ahmad (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2019)
This study aims to determine the effect of communication, bureaucratic structure, implementing attitude, environmental conditions and the size and objectives of the policy on the implementation of the Village Fund Allocation policy in 20 villages in the Central Kuantan Subdistrict of Kuantan Singingi Regency. The population in this study were all villages located in Kuantan Tengah District, Kuantan Singingi Regency, while the respondents consisted of 6 people, namely the Village Head, Village Secretary, Village Treasurer, LPMD, BPD, and Community Leaders, so that the population was 120 people. The sampling method used in this study is saturated sampling method or census method, namely the overall population method. Thus, the number of sampling taken is all members of the population as many as 120 people as respondents. This study uses primary data obtained from questionnaires to respondents. The statistical method used to test the research hypothesis is multiple regression method with software assistance (Statistical Product and Service Solution) version 22.0. The results of the study prove that communication, bureaucratic structure, implementing attitudes, environmental conditions and policy measures and objectives influence the implementation of the Village Fund Allocation policy